Factors associated with chronic kidney disease knowledge and preventive practices: An analytical cross-sectional study among patients with hypertension at Amana Regional Referral Hospital in Dar es Salaam, Tanzania. - Joel Seme Ambikile; Shabani S Ngulupi; Agnes Fredrick Massae (PLoS ONE)
Background Globally, Chronic kidney Disease (CKD) has become a significant public health concern, with sub-Saharan Africa being among the populations experiencing the highest rates. Managing CKD poses a significant challenge due to its health complications and associated high cost of care. Hypertension is one of the leading causes of CKD, responsible for the decline in kidney function in patients. Knowledge and lifestyle modifications are pivotal to the prevention and progression of CKD. In Tanzania, little is known regarding CKD knowledge and preventive practices among patients with hypertension. Therefore, this study aimed to assess context-specific factors associated with CKD knowledge and preventive practices among patients with hypertension at Amana Regional Referral Hospital in Dar es Salaam. Methods An analytical cross-sectional study involving 184 patients was conducted at Amana Regional Referral Hospital. Patient were recruited at the outpatient hypertension clinic using simple random sampling in June and July 2022. Data analysis was conducted using IBM-SPSS Statistics version 25. Bivariate and multiple logistic regression analyses were performed to identify factors associated with knowledge and preventive practices related to CKD, with statistical significance set at a p-value < 0.05. Results The median CKD knowledge score was 13 (IQR: 9-16). Of the 184 respondents, 104 (56.5%) demonstrated high CKD knowledge. None of the sociodemographic factors were significantly associated with CKD knowledge. The median score for CKD preventive practices was 9 (IQR: 8-9), and 111 respondents (60.3%) had good practices. High CKD knowledge was significantly associated with good CKD preventive practices (AOR: 1.98; 95% CI: 1.08, 3.62; p = 0.027). Conclusion A significant proportion of hypertensive patients in this study exhibited both high CKD knowledge and good preventive practices. The positive correlation between CKD knowledge and improved preventive practices highlights the importance of educational interventions to further enhance CKD knowledge among patients with hypertension.